2016
DOI: 10.1016/j.mib.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Type VI secretion and anti-host effectors

Abstract: Secretion systems play a central role in infectious diseases by enabling pathogenic bacteria to deliver virulence factors into target cells. The type VI secretion system (T6SS) mediates bacterial antagonism in various environments including eukaryotic niches, such as the gut. This molecular machine injects lethal toxins directly in target bacterial cells. It provides an advantage to pathogens encountering the commensal flora of the host and indirectly contributes to colonization and persistence. Yet, the T6SS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
198
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(211 citation statements)
references
References 111 publications
8
198
0
5
Order By: Relevance
“…The T6SS has a broad range of cellular targets and uses an armory of toxins and effectors to subvert or kill prey cells (1,2). A bacterial species may carry several T6SSs; for example, three in P. aeruginosa (5), four in Yersinia pseudotuberculosis (23), and six in Burkholderia pseudomallei (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T6SS has a broad range of cellular targets and uses an armory of toxins and effectors to subvert or kill prey cells (1,2). A bacterial species may carry several T6SSs; for example, three in P. aeruginosa (5), four in Yersinia pseudotuberculosis (23), and six in Burkholderia pseudomallei (24).…”
Section: Discussionmentioning
confidence: 99%
“…T6SS | Pseudomonas | RsmA | AmrZ T he type VI secretion system (T6SS) is widely distributed within Gram-negative bacteria and is capable of injecting effector proteins into eukaryotic cells (1). Mounting evidence suggests the primary role of the T6SS is in bacterial warfare (2).…”
mentioning
confidence: 99%
“…Since 77‐kDa VgrG‐2 with no extension domain is required for T6SS assembly (Appendix Fig S3; Pukatzki et al , 2007), there is also enough space for effectors interacting with VgrGs, such as 72‐kDa TseL (Dong et al , 2013), in agreement with the model that many effectors bind to the VgrG/PAAR spike (Fig EV6; Shneider et al , 2013). However, the repertoire of secreted effectors is large (Durand et al , 2014; Alcoforado Diniz et al , 2015; Hachani et al , 2016), and therefore, it is likely that the overall shape of T6SS baseplate will vary between organisms. This could be achieved either by changes in the angle between TssF/G and TssK, or elongating the wedge or TssK assembly with a help of flexible C‐terminal head domain (Nguyen et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A well-established function of the T6SSs is to compete against rival bacteria in polymicrobial environments by delivering "antibacterial" toxins such as cell-wall-degrading enzymes, nucleases, and membrane-targeting enzymes, into target competitor bacterial cells (24)(25)(26)(27). Moreover, some T6SSs associated with pathogens have been reported to be involved in bacterial pathogenesis by translocating "antieukaryotic" effectors into eukaryotic cells to modulate host immunity and inflammation (28)(29)(30)(31). The well-characterized antieukaryotic effectors are several "evolved" VgrG proteins and non-VgrG phospholipases and deamidases (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Moreover, some T6SSs associated with pathogens have been reported to be involved in bacterial pathogenesis by translocating "antieukaryotic" effectors into eukaryotic cells to modulate host immunity and inflammation (28)(29)(30)(31). The well-characterized antieukaryotic effectors are several "evolved" VgrG proteins and non-VgrG phospholipases and deamidases (28)(29)(30)(31). Recently, we reported that the T6SS-4 from Yersinia pseudotuberculosis was involved in zinc transport via secretion of the zincchelating effector YezP into medium (32).…”
mentioning
confidence: 99%